2015
DOI: 10.1590/1516-4446-2014-1518
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological dysfunction in adults with early-onset obsessive-compulsive disorder: the search for a cognitive endophenotype

Abstract: Objective: Evidence suggests that early-onset obsessive-compulsive disorder (OCD) is an etiologically distinct subtype of OCD. The objective of the present work was to search for neurocognitive endophenotypes of early-onset OCD based on assessments of attention, memory, and executive function in patients with the disorder and their unaffected siblings. Methods: We compared the performance of 40 adult patients with early-onset OCD, 40 of their unaffected siblings, and 40 unrelated healthy controls on a neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…The most classical are the Trail Making Task Part B (TMT-B) where the subject has to connect letters and numbers sequentially, alternating between them; and the Wisconsin Card Sorting Test (WCST) where the subject has to classify cards according to an implicit and changing rule. On the TMT-B, the results seem to be inconsistent with some studies finding equal performances between OCD patients and healthy controls [13,19,20,25,34,35,51] while others do not [11,17,30,33]. With the WCST, there is far less inconsistencies, especially with regard to perseverative errors, with a pronounced trend towards poorer performance exhibited by OCD patients [8,11,[14][15][16]19,22,[34][35][36]40,44,45,51,[56][57][58][59][60][61]; even though some studies failed to report this difference [13,21,24,25,31,49,62,63] More recently, computerized tasks were developed to assess behavioral flexibility with more specificity and in a more controlled fashion.…”
Section: Flexibilitymentioning
confidence: 62%
See 2 more Smart Citations
“…The most classical are the Trail Making Task Part B (TMT-B) where the subject has to connect letters and numbers sequentially, alternating between them; and the Wisconsin Card Sorting Test (WCST) where the subject has to classify cards according to an implicit and changing rule. On the TMT-B, the results seem to be inconsistent with some studies finding equal performances between OCD patients and healthy controls [13,19,20,25,34,35,51] while others do not [11,17,30,33]. With the WCST, there is far less inconsistencies, especially with regard to perseverative errors, with a pronounced trend towards poorer performance exhibited by OCD patients [8,11,[14][15][16]19,22,[34][35][36]40,44,45,51,[56][57][58][59][60][61]; even though some studies failed to report this difference [13,21,24,25,31,49,62,63] More recently, computerized tasks were developed to assess behavioral flexibility with more specificity and in a more controlled fashion.…”
Section: Flexibilitymentioning
confidence: 62%
“…Interestingly, Valerius et al [68] found that this prolonged reaction time positively correlates with the severity of Cognitive inhibition is mainly assessed by the Stroop task. Across the literature, while a few studies failed to report a difference using this task [13,20,24,39,50,78,79], the vast majority of studies did [11,15,16,19,22,33,51,56,[80][81][82][83]. More important, the meta-analysis performed by Shin et al [46••], which included 12 studies for this task, confirms the impairment of OCD patients.…”
Section: Flexibilitymentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, other models lead to a novel stereotyped, repetitive pattern of behavior, as is seen with dopaminergic (quinpirole) and serotonergic (8-OHDPAT) agonists that induce perseverative locomotor behavior in the Y-maze or open field chambers (Yadin et al, 1991, Szechtman et al, 1998). Other measures, such as reversal learning or prepulse inhibition deficits, parallel findings that are not explicitly diagnostic but are instead thought to underlie the symptoms of OCD, such as cognitive rigidity or motor inhibition deficits (Chamberlain et al, 2006, Remijnse et al, 2006, Gu et al, 2008, Valerius et al, 2008, Andersen et al, 2010, Ahmari et al, 2012, Bissonette and Powell, 2012, Brigman et al, 2012, Remijnse et al, 2013, Hatalova et al, 2014, Zhang et al, 2015). …”
Section: Validation Of Mouse Models Related To Ocdmentioning
confidence: 94%
“…Regarding Intelligence Quotient (IQ), performance differences were identified in adults, in a recent meta-analysis that pointed not only an IQ difference between patients with OCD and healthy controls but also a larger IQ discrepancy between verbal and performance IQ in the OCD group [21]. Finally, Zhang et al (2015) evaluated the cognitive performance of adults with early-onset OCD and identified impaired inhibitory control and cognitive flexibility in both patients with OCD and their siblings when compared to controls [22].…”
Section: Introductionmentioning
confidence: 99%